Pengetahuan, Profesionalisma, Urutan Bukti Audit dan Audit Judgment - Muhsin Muhsin (FORBISWIRA FORUM BISNIS DAN KEWIRAUSAHAAN - SINTA 4, 2021)
This study aims to analyze the influence of the variables of the examiner ’s knowledge, professionalism, and the sequence of audit evidence on the auditor ’s audit judgment. The research sampling was students of the Accounting Department who passed Auditing 1 and Auditing 2 of FEB UNTAN Pontianak, West Kalimantan, using the purposive sampling method on the condition that the students were able to understand the financial statement audit. Analysis of research data using the WarpPLS 7.0 tool. Research produces auditor knowledge, professionalism, and the sequence of audit evidence that has a positive effect on audit judgment is accepted.